Determinan Minat Wajib Pajak dalam Menerapkan Sistem E-Filling di KPP Pratama Badung Selatan - Pradnyani, Ni Luh Putu Sukma; Jati, I Ketut (E-Jurnal Akuntansi; Vol 31 No 7 (2021)DO - 10.24843/EJA.2021.v31.i07.p18, 2021)
This study aims to obtain empirical evidence of the effect of information technology readiness, perceived usefulness, system effectiveness, and system feasibility on taxpayers' interest in implementing the e-filling system. The Technology Acceptance Model (TAM) and Task Technology Fit (TTF) are used as a theoretical basis to explain the effect of information technology readiness, perceived usefulness, system effectiveness, and system feasibility on taxpayers' interest in implementing the e-filling system. The number of samples used in the study were 100 respondents with purposive sampling method of determining the sample. The analysis technique used is multiple linear regression analysis. The results of the analysis indicate that information technology readiness and system feasibility have a positive and significant effect on taxpayers' interest in implementing the e-filling system, while perceptions of the usefulness and effectiveness of the system have no effect on the interest of taxpayers in implementing the e-filling system. Keywords: Information Technology Readiness; Perceptions of Usefulness; System Effectiveness; System Eligibility; Interest in Implementing the E-Filling System.